Health benefits of anthocyanins against age-related diseases - Ma, Xiaojie; Jin, Zhihai; Rao, Zhijian; Zheng, Lifang (Frontiers in Nutrition, 2025)
Anthocyanins, a class of polyphenol flavonoids widely present in various fruits and vegetables, have attracted significant attention due to their potent anti-inflammatory, antioxidant, and anti-aging properties. Recent studies indicate that anthocyanins may play important roles in extending life and preventing or treating age-related diseases. This review systematically summarizes the chemical characteristics of anthocyanins and their potential roles in age-related diseases, including lifespan extension, neurodegenerative diseases, skeletal diseases, cardiovascular diseases, cancer, and metabolic syndrome. Furthermore, we explore the effects of anthocyanins on age-related diseases and their potential mechanisms of action to establish a theoretical foundation for future clinical applications.